1970
DOI: 10.1180/minmag.1970.037.289.11
|View full text |Cite
|
Sign up to set email alerts
|

The Mössbauer spectra of several micas and related minerals

Abstract: SUMMARY.Well-resolved M6ssbauer spectra of several dioctahedral and trioctahedral micas have been obtained and subjected to detailed computer analysis. Most of the spectra can be resolved into two ferrous quadrupole doublets and one ferric quadrupole doublet. In dioctahedral micas, ferrous iron is seen to occupy the larger, more symmetric octahedral site in preference to the smaller, less symmetric site, confirming predictions made on the basis of structure alone. In trioctahedral micas there is still a tenden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Even an iron-rich smectite, which was effectively reduced, gave rise to only one Fe 2+ doublet (Rozenson and Heller-Kallai, 1976). Two Fe z+ doublets were observed for two muscovites studied by Hogg and Meads (1970) and for six samples investigated in our laboratory (unpublished). According to Annersten the Fe 2+ in glauconites is disordered, in contrast to Fe 3+, which tends to be ordered.…”
mentioning
confidence: 76%
“…Even an iron-rich smectite, which was effectively reduced, gave rise to only one Fe 2+ doublet (Rozenson and Heller-Kallai, 1976). Two Fe z+ doublets were observed for two muscovites studied by Hogg and Meads (1970) and for six samples investigated in our laboratory (unpublished). According to Annersten the Fe 2+ in glauconites is disordered, in contrast to Fe 3+, which tends to be ordered.…”
mentioning
confidence: 76%
“…The points corresponding to sample l saturated with various cations fall on the straight lines, but, for clarity, are not included in the figures. Points corresponding to metabentonite (MB, sample 15) and to pyrophyllite (P), for which the parameters were taken from the literature (Wardle and Brindley, 1970;Hogg and Meads, 1970) and which contain Fe 3+ in M(2) sites only, fall on the straight line of Figure 4, as shown.…”
Section: The Mossbauer Spectramentioning
confidence: 99%
“…On a size basis it would be expected that Fe 2+ would favor the larger trans site; however, preference may be shown for the more readily distorted cis site. Hogg and Meads (1970) suggested that most Fe 2+ in dioctahedral micas occupies the trans sites; it is probable that the same relationship applies in the case of the glauconite (e.g., Rolf et al, 1977) which, although predominantly dioctahedral, may have some trioctahedral character (McRae, 1972). Because most of the octahedral Fe 2+ in glauconite is in the site with the larger QS (see Table 3), the present data suggest that the Fe 2+ occurs preferentially in the trans M(1) site.…”
Section: Interpretation Of the Mrssbauer Spectramentioning
confidence: 99%